Analisis Faktor-Faktor Pembentuk Customer Satisfaction dan Repurchase Intention Konsumen Produk Tas Lokal - Farizka Hayyu Artanti; Usep Suhud; Meta Bara Berutu (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the effects of product design, content marketing, and e-service quality on customer satisfaction and repurchase intention among consumers of the local bag brand Merché. A quantitative research approach was employed using a survey method involving 240 Merché consumers in the DKI Jakarta area. Data were analyzed using Structural Equation Modeling (SEM) with the assistance of SPSS and AMOS software. The results indicate that product design, content marketing, and e-service quality have a positive and significant effect on customer satisfaction. Furthermore, product design and customer satisfaction also have a positive and significant effect on repurchase intention. However, content marketing and e-service quality do not have a significant direct effect on repurchase intention. These findings suggest that customer satisfaction plays a crucial role in encouraging repurchase intention, while product design is the only variable that directly influences both dependent variables. This study contributes theoretically by extending the application of Expectation Confirmation Theory in the context of digital marketing for local fashion brands and provides practical insights for fashion businesses in formulating strategies focused on enhancing customer satisfaction and long-term consumer loyalty